From Angela's Ashes to the Celtic Tiger: Early life conditions and adult health in Ireland - Liam Delaney; Mark McGovern; James P. Smith (University College Dublin, UCD School of Economics, 2009)
We use data from the Irish census and exploit regional and temporal variation in infant mortality rates over the 20th century to examine effects of early life conditions on later life health. Our main identification is public health interventions which eliminated the Irish urban infant mortality penalty. Estimates suggest that a unit decrease in mortality rates at time of birth reduces the probability of being disabled as an adult by between .03 and .05 percentage points. We find that individuals from lower socio economic groups had marginal effects of reduced infant mortality twice as large as those at the top.
hdl:10197/2627
Keywords: I19; N34; 330